Implementation and Evaluation of an Ohmic Heating System to Produce Curd - Kobra Heidarbeigi; Mohammad Hossein Nargesi (Biomechanism and Bioenergy Research)
In the food industry, different heating processes are used to condense and then prevent the corruption of food. Ohmic heating is one of the new methods in which food materials act as electrical resistances. In the method, two electrodes are used to be in contact with food materials, and electricity is transmitted through them. Curd is one of those products that is obtained from heating doogh. The novelty of the present research is producing crud using ohmic heating. An experimental system system was implemented to do this. Then the effects of voltage and electrode on the final temperature and time duration of the crud production process were investigated. The applied voltages were 60, 70, 80, and 90 V, and two electrode types, stainless steel and brass, were tested. The results showed a significant relationship between time duration process and voltage at a 1% probability level, but not for electrode type. The minimum time duration and energy consumption were obtained by steel electrode with 80 V as 57.83 s and 18.97 kJ, respectively.